Migrācija kā Uzbekistānas sociāli ekonomiskās attīstības faktors - Aminaddinova, Komila (Latvijas Universitāte, 2024)
The goal of the thesis is to investigate the impact of migration on socio economic growth in Uzbekistan, a topic that resonates with worldwide migration dynamics while exhibiting distinct regional peculiarities. The study attemptsto analyze the size and dynamics of incoming and outbound migration in Uzbekistan. Examine the economic impact of migration in Uzbekistan, with an emphasis on labor markets, remittances, and regional development. Understand how migration affects family structures and community cohesion. Investigate the gender-specific impacts of migration, focusing on how migration trends affect men and women differently in Uzbekistan. This thesis aims to provide a complete review of migration's multiple repercussions, as well as insights into potential policy changes required to reap the benefits of migration while reducing its obstacles.
Migration as a Factor of Socio-economic Development in Uzbekistan
Keywords: Ekonomika un uzņēmējdarbība; Migration; socio-economic development; Uzbekistan; impact of migration